A COMPARATIVE STUDY OF PRINT AND DIGITAL RESOURCES USAGE IN FEDERAL POLYTECHNIC LIBRARIES IN THE NORTH CENTRAL STATES OF NIGERIA: IMPLICATION FOR COLLECTION DEVELOPMENT - Kaaie, Teghtegh Felix (Current Journal of Library and Information Sciences (CJLIS), 2025)
This study was carried out to compare print and digital resources usage in Federal Polytechnic Libraries in the North Central States of Nigeria. Four objectives and four research questions were formulated to guide the study. The study employed a descriptive survey method. Questionnaire was the instrument used for data collection. The population of the study consisted of a total number of sixty-five thousand three hundred (65,300) students and staff of federal polytechnics in the North Central states of Nigeria. The sample size was three hundred and fifty-three (353) students and staff of Federal Polytechnic Wannune, Benue State. It was revealed from the study that majority of the respondents consult more print resources such as textbooks, government publications, past projects, reference materials, journals than digital resources. The study also revealed that the convenient to use, very easy to retrieve and use and familiarity with print resources were among the top reasons given for the use of print resources. The study recommended that more funds should be allocated to the library to provide both print and digital libraries.